Improving Underwater Image Quality Using WZDN Algorithm - Blessa Binolin Pepsi M; Aswin S (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
In underwater photography, images often suffer from color distortion, haziness, and low visibility due to the scattering of light by water and particles. To address these issues, we propose using advanced algorithms designed specifically for underwater conditions. Our approach involves correcting color distortion and restoring accurate color representation using a method called Wavelength Dehazing Zero Deep Network (WZDN). This algorithm enhances visibility and improves color fidelity by removing haze and adjusting colors to their true values. Additionally, we implement techniques to enhance contrast, making underwater details more visible and improving overall image quality. By reducing the impact of particulate matter and dissolved substances, we minimize haziness and murkiness, resulting in clearer images. Furthermore, our algorithms are optimized for efficient real-time processing, making them suitable for applications requiring rapid image enhancement, such as underwater exploration, surveillance, and marine research. our research focuses on developing algorithms that enhance underwater images by correcting color distortion, improving visibility, and reducing haziness. These algorithms, particularly WZDN, provide superior color fidelity and enhanced visibility, ultimately restoring the clarity of underwater images.